2010
DOI: 10.1007/s10545-010-9075-9
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of neuropathic lysosomal storage disorders

Abstract: Although neurodegenerative diseases are most prevalent in the elderly, in rare cases, they can also affect children. Lysosomal storage diseases (LSDs) are a group of inherited metabolic neurodegenerative disorders due to deficiency of a specific protein integral to lysosomal function, such as enzymes or lysosomal components, or to errors in enzyme trafficking/targeting and defective function of nonenzymatic lysosomal proteins, all preventing the complete degradation and recycling of macromolecules. This primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
101
0
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(111 citation statements)
references
References 160 publications
(210 reference statements)
0
101
0
10
Order By: Relevance
“…Mutations in the Cln2 gene result in deficiency or loss of function of the TPP1 enzyme (9,30,35). There have been reports of over 68 missense mutations in the Cln2 gene, including 35 single amino acid substitutions.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the Cln2 gene result in deficiency or loss of function of the TPP1 enzyme (9,30,35). There have been reports of over 68 missense mutations in the Cln2 gene, including 35 single amino acid substitutions.…”
Section: Discussionmentioning
confidence: 99%
“…In these diseases, a defi ciency of hexosaminidase A and/or B leads to a buildup of GM2 that leads to neurodegeneration. Both diseases are associated with development of Lewy bodies and synuclein aggregates ( 7,8 ). As in the case of GlcCer, GM2 also has been shown to interact with synuclein and may contribute to neurodegeneration via a similar feedback loop, as proposed for glucocerebrosidase and synuclein ( 49,50 ).…”
Section: Approaches To Therapeutic Interventionmentioning
confidence: 87%
“…More than 50 LSDs are known and are usually classifi ed according to the nature of the accumulating substrate. Pathology in the CNS is a common feature of most LSDs ( 7,8 ). While the best example of this is the link between Gaucher's disease (GD) and parkinsonism, the link between other LSDs and PD is suggested, but less well documented due to the small number of patients ( 8 ).…”
mentioning
confidence: 99%
“…Lysosomal enzymes are ubiquitously distributed, but substrate storage is usually restricted to cells, tissues and organs with higher substrate turnover. Recently, it has been suggested that the primary gene defect and substrate storage are triggers of a complex cascade of events that lead to many of the disease manifestations (Bellettato & Scarpa, 2010). In this context, secondary substrate storage, perturbations of Calcium homeostasis and lipid trafficking would contribute to disease pathogenesis.…”
Section: Introductionmentioning
confidence: 99%